Slow shell building, a possible trait for resistance to the effects of acute ocean acidification. (10th June 2016) - Waldbusser, George G.; Gray, Matthew W.; Hales, Burke; Langdon, Chris J.; Haley, Brian A.; Gimenez, Iria; Smith, Stephanie R.; Brunner, Elizabeth L.; Hutchinson, Greg
Abstract: Increasing anthropogenic carbon dioxide is altering marine carbonate chemistry through a process called ocean acidification. Many calcium carbonate forming organisms are sensitive to changes in marine carbonate chemistry, especially mollusk bivalve larvae at the initial shell building stage. Rapid calcification, limited energy reserves, and more exposed calcification surfaces, are traits at this stage that increase vulnerability to ocean acidification through our previously argued kinetic‐energetic hypothesis. These developmental traits are common to broadcast spawning bivalve species that are the focus of most ocean acidification studies to date. Some oyster species brood their young, which results in slower development of the embryos through the initial shell formation stage. We examined the responses of the brooding Olympia oyster, Ostrea lurida, during their initial shell building stage. We extracted fertilized eggs from, O. lurida, prior to shell development, then exposed developing embryos to a wide range of marine carbonate chemistry conditions. Surprisingly, O. lurida showed no acute negative response to any ocean acidification treatments. Compared to the broadcast spawning Pacific oyster, Crassostrea gigas, calcification rate and standardized endogenous energy lipid consumption rate were nearly 10 and 50 times slower, respectively. Our results suggest that slow shell building may lessen the energetic burden of acidification at this stage and provides additional support for our kinetic‐energetic hypothesis. Furthermore, these results may represent an example of exaptation; fitness conveyed by a coopted trait that evolved for another purpose, a concept largely lacking in the current perspective of adaptation and global climate change.